Study on texture evolution and properties of silver thin films prepared by sputtering deposition - Jung, YS (ELSEVIER SCIENCE BV, 2004)
By observing XRD profiles, the evolution of the crystallographic orientation of silver thin films was monitored. Sputtering process conditions such as working pressure, deposition power and substrate temperature significantly influenced the relative fraction of the grains with (I 1 1) orientation (lowest energy plane in FCC structure). Sputtering conditions for higher adatom mobility such as moderate range of sputtering pressure (0.14-0.71 Pa) and higher deposition power resulted in more (111)preferred orientation. The Ag thin films deposited under those conditions showed lower resistivity, higher film density, and optical reflectance. These phenomena were explained from the change of adatom mobility with varied process parameters. Higher adatom mobility could be obtained under moderate range of sputtering pressure and higher sputtering power. Higher adatom mobility promoted the growth of (I I I)-oriented grains at the expense of other grains, and resulted in higher film density and improved electrical and optical film properties. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: PREFERRED ORIENTATION; ION-BOMBARDMENT; GROWTH; TIN